A probable Pleistocene pangolin (Order: Pholidota) trackway from South Africa’s Cape south coast - Charles W. Helm; Andrew S. Carr; Hayley C. Cawthra; #oma Daqm; Jan C. De Vynck; Pieter-Jan Gräbe; /uce Nǂamce; Clive R. Thompson (South African Journal of Science)
A fossil trackway, attributed to a probable pangolin trackmaker, has been identified on a Pleistocene aeolianite surface of the Waenhuiskrans Formation in the Bosbokfontein Private Nature Reserve on South Africa’s Cape south coast. The trackway consists of eight tracks and two probable tail traces. This appears to be the first description of a pangolin trackway in the global fossil record. The trackway was probably registered during Marine Isotope Stage 6 or 5. Trackway assessment and interpretation involved the integration of indigenous African and Western-based ichnological approaches, leading to a reasonably confident conclusion on the probable trackmaker’s identity. Alternative trackmakers (felids, viverrids and canids) were considered, but excluded or regarded as less likely candidates. There are three Cenozoic body fossil records of pangolins from the southwestern Cape, which have been assigned to the giant pangolin (Smutsia gigantea). Only Temminck’s pangolin (Smutsia temminckii) currently occurs in southern Africa. All eight extant pangolin species are considered to be threatened with extinction according to the IUCN Red List of Threatened Species.